Bioprospection of Metagenome to Access Novel Biological Pathways - Gosse, Jessica Thandara (Université d'Ottawa / University of Ottawa, 2019)
This research is focused on finding new secondary metabolites from bacterial sources through genome mining, allowing the study of unknown molecules that could be potential candidates for use as drugs against microbial infections, cancer, and immune diseases. Bioprospection was conducted through targeted environmental sampling, unusual environments exploration and molecular and computational biology. In the first project, an environmental DNA (eDNA) fosmid library from urban soil samples was built and arrayed for the presence of potential gene clusters. In total, 7% of the library was positive for the presence of secondary metabolite pathways. Sequencing revealed genetic similarity with other organisms that belong to urban areas, showing adaptation of the microbiota to anthropogenic environments. The second project focuses on the heterologous expression of a lantipeptide from a bacterial isolate from an urban environment. Using a Multigene Expression System (MES), different components of the biosynthetic pathway were cloned and expressed. We were able to successfully express the genes responsible for lantipeptide tailoring but the lantipeptide portion of the pathway was not obtained with the methods used. The last project examined cave bacterial secondary metabolite production and organism diversity to determine the relationship between the microbiome and to retrieve potential active natural compounds. Through sequence analysis and LC-ESI-HRMS, several metabolites were detected and their potential role for the cave microbiome could be established.
Keywords: bioprospection; novel natural products